Association between the triglyceride-glycated hemoglobin index and diabetes risk among patients with Non-alcoholic fatty liver disease: A longitudinal cohort study - Cuimei Wei; Changchun Cao; Zengxin Xu; Gang Chen; Wenjing Liu; Miao Zhang; Haofei Hu; Shanghua Xu (PLoS ONE, 2026)
Background Emerging evidence suggests that the triglyceride-glycated hemoglobin index (TyH-i) may be a novel predictor of type 2 diabetes (T2D) risk. However, in patients diagnosed with NAFLD, the precise link between TyH-i and T2D is still not well elucidated. Currently, the literature lacks sufficient research on how this index affects the incidence of diabetes in the NAFLD population, highlighting a significant gap in our understanding of the interactions between these metabolic conditions. This research seeks to evaluate the association between the TyH-i and diabetes risk, as well as to investigate its predictive capability in patients with NAFLD concerning the triglyceride-glucose index (TyG-i). Methods Based on the data of 2741 participants who had no diabetes at baseline and suffered from NAFLD, leveraging a nationwide retrospective cohort, we derived the TyH-i as the natural logarithm of [HbA1c (%) × fasting TG (mg/dL) ÷ 2].To assess the relationship between TyH-i and the risk of developing T2D, a Cox proportional hazards regression model was used to estimate the hazard ratio (HR) and 95% confidence interval (CI). Furthermore, the nonlinear correlations between them were also investigated using the restricted cubic spline model. We gauged the relative discriminatory capacity of TyH-i versus TyG-i by constructing time-dependent receiver-operating characteristic (ROC) plots and comparing the corresponding areas under the curve (AUC) with their 95% CI. Results In a median follow-up duration of 5.21 years, incident diabetes was recorded in 223 individuals. The multivariable-adjusted analysis revealed that each unit increase in TyH-i corresponds to a 46% elevation in diabetes risk (HR: 1.75; 95%CI: 1.28-2.41; P = 0.0005). Additionally, a U-shaped relationship was identified between TyH-i levels and the occurrence of type 2 diabetes. Specifically, TyH-i values below 4.95 displayed a notable inverse association with the risk of type 2 diabetes (HR: 0.20, 95%CI: 0.05-0.78, P = 0.0206). Conversely, an elevation in TyH-i levels beyond this threshold was linked to a higher risk of developing type 2 diabetes (HR: 2.01, 95% CI: 1.45-2.39, P < 0.0001). Furthermore, the findings indicate that the Youden Index for both TyH-i and TyG-i is nearly identical, implying that TyH-i may serve as a valid marker for diabetes diagnosis. Conclusion Among the patient population suffering from NAFLD, the initial TyH-i level demonstrated a U-shaped correlation with the emergence of type 2 diabetes. This indicated inflection point can act as a practical clinical threshold, allowing differentiation between individuals at low and high risk. The findings imply that keeping TyH-i close to this inflection may play a role in mitigating the progression to diabetes among NAFLD patients.